Synthesis of derivatives of complex signals based on nonlinear discrete sequences with improved correlation properties - Gorbenko, I.D.; Zamula, A.A.; Luc, Ho Tri (Radiotekhnika, 2019)
The structure of modern information and communication systems (ICS) is characterized by considerable spatial diversity of a large number of interacting subscribers. In these conditions, technologies of processing, storage, protection, transmission and reception of information on the network under conditions of natural and artificial interferences (impacts), as well as limited frequency and energy resources of ICS play an extremely important role in ensuring the quality of service of end users. ICS, especially for critical applications, are increasingly demanding to ensure the effectiveness of their functioning (speed of information transmission, electromagnetic compatibility, noise immunity, information security, survivability, secrecy, information security). The ability to implement these requirements is largely disregarded by applicable information technology. There is a contradiction between the strict requirements for secrecy, confidentiality, integrity, authenticity of data stored and transmitted through communication lines, on the one hand, and existing models, methods and technologies for managing telecommunications networks, information security, services and quality of service, on the other hand. The main ways to resolve this contradiction is to increase the noise immunity, secrecy and information security of ICS based on the improvement of methodological bases for the construction of ICS by developing methods of information exchange, methods of synthesis of signals of physical data carriers with the necessary properties. The principles of construction of derivative signal systems are given. The requirements for output and source signals are defined. The justification of the possibility of using random (pseudorandom) processes for the production of signals is used to construct them. The results of studies of ensemble, correlation, and structural properties of the obtained systems of derivative signals are presented. It is shown that the use of this class of complex nonlinear discrete signals in modern ICS will improve such performance indicators of such systems as noise immunity, information and structural stealth.